Necessary Conditions for Aggregation in Securities Markets - Brennan, M. J.; Kraus, Alan (Journal of Financial and Quantitative Analysis, 1978)
An important aggregation problem is the derivation of equilibrium security prices which are independent of the allocation of initial wealth among investors. The problem is of interest because, if investors are conceived as being endowed with initial holdings of securities, it is clear that the initial wealth allocation which depends on security prices is endogenous to the model. Although he addresses a differently defined objective, Rubinstein [8] has shown that sufficient conditions for the solution of the problem described above are conditions that permit construction of “composite” (representative) investors whose resources, beliefs, and tastes depend on the exogenous specifications of the economy (viz., the beliefs and tastes of all investors and production conditions) but not on the initial allocation of securities.